Pelatihan Komunikasi Efektif untuk Meningkatkan Kemampuan Softskill Siswa SMK Al-Aziziyah Kwanyar sebagai Bentuk Pendampingan dalam Persiapan Memasuki Dunia Kerja - Wibowo, Wasis Purwo; Nindhita, Vidya; Sovirilla, Rahma Farida; Safii, Hoyruh Niswatin (Keris: Journal of Community Engagement, 2024)
Effective communication training enhances the soft skills of vocational high school students by fostering the development of communication skills, a crucial component of the soft skills that employers increasingly demand. This training aims to equip and prepare students to face the demands of the world of work. The training method used is to combine theoretical and practical approaches, including simulations, group discussions, and exercises as a form of evaluation. Through this training, students gain an understanding of increasing self-confidence, the ability to work in a team, and the skills to convey ideas effectively. The results of this training are expected to provide a significant increase in students' communication skills, which in turn will increase competitiveness in the world of work when they graduate later.